On the optimal allocation of grants to energy conservation investments - Magirou, Vangelis F. (Resources and Energy, 1984)
A criterion is presented for the allocation of grants by a state agency to energy conservation investments which maximizes the expected value of the resulting energy savings, subject to a constraint on the total expenditure for these grants. The allocation formula that follows from the application of the above criterion has certain properties that do not depend on the precise value of the relevant parameters and which are a desirable feature of any grant allocation scheme.